Endomarketing educacional: um processo gerencial de estratégia competitiva - Caruso, Michelle Antunes (Universidade do Vale do Rio dos Sinos, 2011)
This End-of-Study Masterpiece consists of discovering if the internal marketing can contribute for the perception of quality of an institution of education next to its pupils (students). This analysis is made from a bibliographical research on administration, marketing, motivation, endomarketing, education and young. As theoretical base, authors as Philip Kotler, Idalberto Chiavenato, Saul Bekin, Daniel Coast, Otaíza Romanelli and others had been used. To reach the objective of this study, empreendidas entrevistas em profundidade com alunos, professores e funcionários administrativos da unidade de análise deste trabalho interviews in depth with administrative pupils, teachers and employees of the unit of analysis of this work, the Universitário Course, Lindoia headquarter, had been undertaken. Related to the findings, it can be mentioned that the quality of the educational rendering of services is perceived by the consumer through the attendance carried through the employees of the administrative proceedings and mainly for the teachers, which the pupils associate that the motivation is perceived through the assistance offered and of the interaction proportionated in class and even out of it, in social nets and breaks of the lessons.
Keywords: Administração; Marketing; Endomarketing; Consumidor; Educação; Administration; Marketing; Endomarketing; Consumer; Education